Critical Evaluation of Lecithin-Tween 80 Parenteral Emulsion: Challenges in Maintaining Droplet Size Post-Sterilisation - Milala, Alasen Sembiring; Aryani, Ni Luh Dewi; Purnomo, Ika Angelina (Indonesian Journal of Science and Pharmacy, 2026)
Parenteral emulsions are essential for patients with gastrointestinal disorders. Lecithin benefits liver function, but formulating sterilisation-stable emulsions while maintaining safe droplet size remains challenging. The objective of this study was to evaluate the physical stability of a lecithin-Tween 80 combination parenteral emulsion following sterilisation, focusing on droplet size as a critical parameter. Formulation contained lecithin (5%), Tween 80 (20%), isopropyl myristate (9%), propylene glycol (1%), nipagin (0.18%), nipasol (0.02%), and cassava starch (2.5%) in Water for Injection. Emulsion was prepared mechanically using a multimix mixer at 1500 rpm. Three bottles were sterilised by autoclaving (115°C, 30 minutes); one bottle remained unsterilised as control. Seven-day evaluation assessed organoleptic properties, pH, viscosity, droplet size, creaming, and sterility. Statistical analysis used T-test and one-way ANOVA. Sterilisation significantly increased droplet size (p<0.05), from 5.90±0.45 μm to 8.48±0.62 μm. White precipitate (cassava starch) formed in all preparations from day 2. pH remained stable (5.00-5.42). Viscosity decreased by 47% (111.04 cP to 58.86 cP). Sterility testing revealed microbial growth. The lecithin-Tween 80 parenteral emulsion containing cassava starch requires further optimisation. Key concerns include selecting a more suitable stabiliser, adjusting pH, and sterilising raw materials prior to formulation. This study offers valuable insights for developing future parenteral emulsion preparations.